Is gasoline price elasticity in the United States increasing? Evidence from the 2009 and 2017 national household travel surveys - Frank Goetzke; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Drawing on the 2009 and 2017 waves of the National Household Transportation Survey, this paper models the determinants of vehicle miles traveled, with the aim of parameterizing the magnitude of the fuel price elasticity. To capture changes in this magnitude over the two years of the survey, our specification interacts the logged fuel price with a dummy indicating the 2017 survey year. We find a small but statistically significant mean elasticity of about -0.05 for the year 2009, which increases over fourfold to -0.23 by the year 2017. We explore the robustness of this result to different model specifications and estimation techniques, including instrumental variable estimation to account for the possible endogeneity of fuel prices, as well as quantile regression to account for heterogeneity according to driving intensity. A similar pattern of substantially increasing elasticity emerges across all these models. We speculate that one possible source of this pattern is economic duress from the 2008 financial crisis, which the data suggests reoriented mode choice patterns. – – Ausgehend von den Wellen 2009 und 2017 des "National Household Transportation Survey", modelliert dieses Papier die Determinanten der gefahrenen Fahrzeugmeilen, mit dem Ziel, die Elastizität des Kraftstoffpreises zu parametrisieren. Um einen Wechsel in dieser Bestimmungsgröße über die zwei Jahre der Umfrage zu erfassen, verknüpft unsere Spezifikation den protokollierten Kraftstoffpreis mit einem Dummy für das Erhebungsjahr 2017. Wir finden eine kleine, aber statistische signifikante Elastizität von etwa -0,05 für das Jahr 2009, die sich bis zum Jahr 2017 auf -0,23 vervierfacht. Wir untersuchen die Robustheit dieses Ergebnisses mit verschiedenen Modellspezifikationen und Schätzverfahren, einschließlich instrumenteller Variablenschätzung zur Berücksichtigung der möglichen Endogenität der Kraftstoffpreise sowie einer Quantilsregression zur Berücksichtigung der Heterogenität entsprechend der Fahrintensität. Ein ähnliches Muster einer wesentlich substanziell zunehmenden Elastizität ergibt sich bei all diesen Modellen. Wir vermuten, dass eine mögliche Quelle für dieses Muster die wirtschaftliche Belastung der Haushalte durch die Finanzkrise 2008 ist.
Keywords: D12; Q41; R48; 330; fuel price elasticity; household VMT; heterogeneity